Neighborhood disorder development across the life-course and its relevance for predicting offending - Wojciechowski, Thomas (Criminal justice studies, 2021)
Research has indicated a relationship between neighborhood disorder and risk for offending, but little has taken a developmental perspective. Group-based trajectory modeling was used to identify latent developmental patterns of exposure to community disorder during adolescence and adulthood. Negative binomial regression and logistic regression were used to examine the impact that exposure to neighborhood disorder had for predicting offending outcomes in adulthood. Results indicated that a two-group model best fit the data, with both groups demonstrating a great deal of stability. Assignment to the High group was associated with significantly greater offending frequency and odds of offending in adulthood.